Antenatal management of pulmonary hyperplasia (congenital cystic adenomatoid malformation). (22nd July 2010) - Ankers, D; Sajjad, N; Green, P; McPartland, J L
Abstract : A 26-year-old lady was seen in antenatal clinic. Her anomaly scan at 20 weeks showed significant fetal abdominal ascites and an enlarged echo bright right lung with cardiac displacement. These findings were consistent with recognised type III congenital cystic adenomatoid malformation (CCAM). An induction of labour was undertaken at 32 weeks' gestation due to increasing maternal morbidity. Labour was complicated by abdominal dystocia and a fetal paracentesis was performed, draining 800 ml. A bradycardia developed and the baby was ultimately stillborn. Post mortem examination the right lower lobe bronchus was atretic. The features were typical of those traditionally described as type III CCAM, but in the context of bronchial atresia, are better described as pulmonary hyperplasia.